2019
DOI: 10.1016/j.ijsolstr.2019.02.017
|View full text |Cite
|
Sign up to set email alerts
|

The effect of spiral cold-bending manufacturing process on pipeline mechanical behavior

Abstract: Large-diameter steel pipes, fabricated through the spiral-welding manufacturing process, are extensively used in onshore pipelines for the transmission of energy (hydrocarbon) and water resources. However, their use in demanding applications, such as geohazard areas or in offshore applications has been very limited. Safeguarding the structural integrity in such areas of those pipes requires an efficient strain-based design framework. Bending deformation capacity in the presence of internal pressure is the majo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Since the spiral cold forming process involves large bending deformation of the strip, and the diameter of the formed hollow rods is very small (40-100 mm) [35], so there are higher requirements on the plasticity and toughness of the material. Taking cold-rolled Q195 galvanized steel strip as the experimental object, the mechanical properties and chemical composition are shown in table 1.…”
Section: Experimental Materials Characteristicsmentioning
confidence: 99%
“…Since the spiral cold forming process involves large bending deformation of the strip, and the diameter of the formed hollow rods is very small (40-100 mm) [35], so there are higher requirements on the plasticity and toughness of the material. Taking cold-rolled Q195 galvanized steel strip as the experimental object, the mechanical properties and chemical composition are shown in table 1.…”
Section: Experimental Materials Characteristicsmentioning
confidence: 99%
“…To account for material inelastic behavior, a von Mises plasticity model with isotropic hardening is considered. Furthermore, residual stresses are inserted in the finite element model as initial stresses before the application of bending loading, as calculated from a detailed simulation of the cold bending mechanism (including de-coiling process), which is presented in detail elsewhere [42], and is described briefly in the Appendix. Finally, before the application of internal pressure and bending loading, a hydrotesting loading step is performed corresponding to hydrotesting of the spiral-welded pipe in the pipe mill.…”
Section: Numerical Model Descriptionmentioning
confidence: 99%
“…An extensive investigation on the influence of hydrotest on the structural response of spiral-welded pipes is presented in [42]. The results have shown that hydrotest reduces the residual stresses from the manufacturing process and, as a result, it affects pressurized bending response of the pipe.…”
Section: Effect Of Internal Pressure and Hydrotestingmentioning
confidence: 99%
See 1 more Smart Citation